A Novel Deep Framework for English Communication Based on Educational Psychology Perspective - Wang, Ying; Zheng, Liang (Frontiers in Public Health, 2022)
The impact of verbal reading practices on learning is examined from the perspective of educational psychology, using the motivation theory and the schema theory. This research intends to enhance learner's English communication abilities in response to the needs for national economic growth and scientific and technological development. To motivate students to improve their English, the research may address the issue of inadequate opportunities by adding an artificial intelligence (AI) conversation mechanism to the students speaking English exercise. First, cognitive psychology is analyzed in detail, and a model based on cognitive psychology is implemented to solve the problems existing in student’s English communication. In addition, various measures are presented and used to increase student’s oral English communication abilities. We used sixty students from North China University of Water Resources and Electric Power are separated into two classes: Class A and Class B. The experimental group is called Class A, while the control group is called Class B. Following a comparison of the outcomes obtained before and after training. The experimental group's reading comprehension, responding to questions, situational conversation, and subject description scores rose by 13.33 %, 15.19 %, 17.39 %, and 28.3 %, respectively. The overall average score of the class climbed by 17.75 %, whereas the scores of pupils in Class B improved just an undersized. The results reveal that following the vocalized reading exercise, the student's English grades, self-efficacy, and topic knowledge increased considerably in the experimental group. Moreover, the proposed model, employs computer simulation in the English communication teaching system and AI, which can aid in the creation of an interactive learning environment for students to improve their spoken English and English communication abilities.